1995
DOI: 10.1164/ajrccm.151.2.7842197
|View full text |Cite
|
Sign up to set email alerts
|

Rapid decline in FEV1. A new risk factor for coronary heart disease mortality.

Abstract: Coronary heart disease (CHD) is the leading cause of mortality in the United States. The present cohort study was conducted to determine whether rate of FEV1 loss independently predicts CHD mortality in apparently healthy men. White male Baltimore Longitudinal Study of Aging (BLSA) participants without CHD underwent clinical evaluation at 2-yr intervals; 883 had satisfactory pulmonary and lipid studies and returned for a least one visit. Cases were BLSA subjects without CHD on entry who died a "coronary death"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
93
1
2

Year Published

1997
1997
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(103 citation statements)
references
References 0 publications
5
93
1
2
Order By: Relevance
“…The direct relationship between chronic lung disease such as emphysema and the incidence of CVD has been known for many years (8)(9)(10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%
“…The direct relationship between chronic lung disease such as emphysema and the incidence of CVD has been known for many years (8)(9)(10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%
“…In the Malmo ''men born in 1914 study,'' there were 56 cardiovascular events per 1,000 person-years in smokers in the highest tertile of decline in FEV 1 , and 22.7 in the group with the lowest tertile (12,13). The Baltimore Longitudinal Study of Ageing (14) showed that those individuals who had the most rapid decline in FEV 1 over a follow-up period of 16 years were three to five times more likely to die from a cardiac cause than those who had the slowest decline in FEV 1 . This association was also found even among lifetime nonsmokers, suggesting that the relationship between change in FEV 1 and cardiovascular events is independent of the effects of smoking.…”
mentioning
confidence: 99%
“…Lung function naturally starts to decline at the age of 30 years (Quanjer et al 2012), and accelerated decline in adult life was repeatedly associated with increased mortality, not only due to cardiovascular and respiratory disease (Tockman et al 1995) which could be attributable to smoking but also with all-cause mortality and in never smokers (Mannino et al 2006;Ryan et al 1999). According to recent findings from the British Whitehall study, the direct effects of smoking only explain 4.9 % of the association between lung function and mortality, whereas 21.3 % could be attributed to inflammatory processes in the body and a further 9.8 % to lifestyle factors including nutrition and body fitness (Sabia et al 2010).…”
Section: Introductionmentioning
confidence: 99%